Influence of Partial Er Substitution for Sc on the Microstructure, Mechanical Properties and Corrosion Resistance of Short-Processed Al-4.7Mg-0.6Mn-0.3Zr-0.3Sc Sheets - Guangxi Lu; Yabo Liang; Cong Xu; Wenfei Rao; Yaodong Xue; Longfei Li; Li Zhang; Shaokang Guan (Metals)
Standard AA5083 (ZSE000), AA5083 modified with 0.3 wt.% Zr and 0.3wt.% Sc (ZSE330) and AA5083 modified with 0.3 wt.% Zr, 0.2wt.% Sc and 0.1wt.%Er(ZSE321) sheets were fabricated through a short process (including a simulated twin-belt continuous casting, subsequent direct rolling, intermediate annealing, cold rolling and stress-relief annealing) to systematically investigate the influence of partially substituting Er for Sc on the microstructure, mechanical properties and corrosion resistance of short-processed Al-4.7Mg-0.6Mn-0.3Zr-0.3Sc sheets. The results show that ZSE321 presents the optimal tensile properties (UTS: 541 MPa; 0.2%PS: 469 MPa and EF:7.7%) among the three experimental sheets. This is attributed to significant grain refinement, the inhibition of the recrystallization and promotion on the precipitation of Al3(Sc, Zr, Er) nanoparticles. Furthermore, the corrosion properties of the experimental sheets were also explored in this study, and the short-processed ZSE321 sheet presents the optimum corrosion resistance.